Human resources management in international context. With special reference to the UK,Spain and Turkey - Çakır, Armağan Emre (My University, 1999)
Tez, Yngiltere, Yspanya ve Türkiye'de ?u an varolan ortamlaryn Ynsan Kaynaklary Yönetimi uygulamalary için uygun olup olmady?yny sorgulamakta ve bu ortamlary birbiriyle kar?yla?tyrmaktadyr. Genelde Ynsan Kaynaklary Yönetimi özelde de Kar?yla?tyrmaly Ynsan Kaynaklary Yönetimi konularynda bilgi veren bir Giri? bölümünün ardyndan, Clark ve Mallory tarafyndan geli?tirilen bir biçe kullanylarak üç ülkedeki ortam Uluslararasy Kurumsal Ba?lam (AB, ILO ve OECD), Ulusal Örgütsel Ba?lam (ekonomik dizge, e?itim dizgesi, finans, hukuk dizgesi ve siyasal dizge) ve Ulusal Ekin temelinde kar?yla?tyrylmaktadyr. Her bir temeldeki kar?yla?tyrma, Türkiye'de Ynsan Kaynaklary Yönetimi uygulamalaryny çevreleyen ortamyn di?er iki ülkedekinden çok da kötü olmady?yny göstermektedir. Ancak, her alanda düzeltmelere gereksinim oldu?u ortaya çykmaktadyr. Sonuç bölümünde ilkin, Türkiye'deki ortamyn Ynsan Kaynaklary Yönetimi'ne özellikle gereksinim duyulmasyny gerektiren özel durumu anlatylmakta, ardyndan i?yerlerinin, sendikalar ve i?veren kurulu?larynyn, meslek örgütleri ve benzer kurumlaryn ve son olarak da devletin bu ba?lamdaki 'görevleri' syralanmaktadyr. Bu resim içinde en büyük sorumlulu?un i?yerlerine dü?tü?ü görülmektedir. Ancak di?erleriyle kar?yla?tyryldy?ynda Ynsan Kaynaklary Yönetimi konusunda en ilerici ve yeni dü?ünce ve uygulamalar da yine i?yerlerinden gelmektedir. The thesis questions the suitability of the environments for Human Resources Management practices in three countries namely the UK, Spain and Turkey, and compares these environments with each other. After an introduction presenting the general notions of Human Resources Management in general, and Comparative Human Resources Management in particular, by using a comparative model devised by Clark and Mallory, the environments in the three countries are compared on the basis of International Institutional Context (the EU, ILO and OECD), National Institutional Context (economic system, educational system, finance, legal system and political system) and National Culture. Each comparison on these bases reveals that the environment surrounding Human Resources Management practices in Turkey is not much less favourable than those of the other two countries. Reforms, however, should be realised in every area. In the Conclusion section, first, the special condition of the environment in Turkey that specifically necessitates Human Resources Management is expressed, and then, the respective 'duties' of firms, trade unions and employers' associations, professional associations and similar bodies, and state are identified. Firms appear to have the primary responsibility in this depiction. But, compared to the other actors, they are also the ones who actually do try on most progressive and novel ideas and practices in the field of Human Resources Management.
Keywords: Genel yönetim; İNSAN KAYNAKLARI; YÖNETİM; Yürütmenin yönetimi